Efficiency of the Metropolitan Region of Campinas under the environmental, economic and social perspectives - Ferreira, Denise Helena Lombardo; Morais, Ingrid Metzner (Revista Hipótese, 2019)
It is increasingly necessary to think of solutions so that cities meet the context of sustainability. In this sense, the objective of this research is to verify the efficiency of the municipalities that compose the Metropolitan Region of Campinas from the environmental, economic and social perspectives. For this purpose, the Data Envelopment Analysis (DEA) tool was applied using the CCR and BBC input-oriented models available in the Microsoft Excel - DEA Frontier Program. The results obtained with the use of the CCR models indicate that the cities Jaguariúna and Paulínia were the most efficient in the three perspectives, while in the VRS model, the cities were Jaguariúna, Paulínia, Valinhos and Vinhedo.